Sunna Hadat: Upacara Perubahan Status Kedewasaan Sosial Masyarakat Muslim Alor Kecil Nusa Tenggara Timur - Sastri Sunarti; Ninawati Syahrul; Atisah; Maura Nur Sabrina; Maria Christina Anandya Prijandoko; Ahmad Zaidan Ifkar Hasbi (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2026)
The practice of male circumcision is celebrated through the Sunna Hadat ritual by a Muslim community living within a predominantly Christian and Catholic society. This article examines Sunna Hadat as an oral tradition and a mechanism of social reproduction, as well as the dynamics of interreligious tolerance surrounding its enactment. As an oral tradition, Sunna Hadat incorporates mantras, prayers, and customary chants transmitted genealogically through customary institutions and performed by elders, religious leaders, and the nuclear family. While its narrative structure remains relatively stable, variations in diction and symbolic emphasis occur across generations. Transformations are evident in linguistic adjustments, ritual duration, and the stronger integration of formal Islamic elements compared to earlier practices. Using a cultural studies approach, particularly the theory of representation developed by Stuart Hall and the concept of rites of passage introduced by Arnold van Gennep, this study demonstrates that Sunna Hadat affirms social transition and reflects ongoing identity negotiation in a multireligious context.